Beyond Silence and Stigma: A Systematic Review of Parents’ Lived Experiences, Community Knowledge, and Intellectual Disability - Hussein Hussein (International Disability Innovation Journal, 2026)
Stigma surrounding intellectual disability remains a persistent and multidimensional barrier shaping the lives of children with disabilities and their families. Parents frequently occupy a liminal position where personal caregiving experiences intersect with community attitudes, institutional practices, and structural inequalities. This systematic review synthesizes international literature examining parents’ lived experiences of stigma, community knowledge, and misconceptions, and their implications for family well-being, social participation, and inclusive education. Drawing on peer-reviewed studies published between 2003 and 2025, the review integrates evidence from disability studies, mental health, sociology, and inclusive education. Findings indicate that stigma operates at interpersonal, institutional, and structural levels, often manifesting as courtesy stigma, surveillance of parental competence, and exclusion from educational and social systems. However, the review also identifies forms of parental resistance, advocacy, and meaning-making that challenge deficit-based narratives. By bringing together fragmented bodies of literature, this review advances an integrated conceptual understanding of stigma as a relational and socially produced phenomenon rather than an individual deficit. The paper concludes with implications for inclusive education policy, community-based stigma reduction, and future research, emphasizing the need to center parents’ voices while addressing the broader socio-structural conditions that sustain stigma.